Answer:
![\left \{ {{3x+3y=0} \atop {7x-y=8}} \right.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/36lbwhybjxsujf5khss84185asx4qq2h4b.png)
Explanation:
An equivalent system refer to other system that has the same values for the variables, or it's satisfied by the same values. First, we calculate what are the values for x and y, in the given system.
![\left \{ {{3x+3y=0} \atop {-4x+4y=-8}} \right.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1xrdw1y9prflewyd8xphlw1tf4wbd0rg5w.png)
Extracting common factors:
![\left \{ {{3(x+y)=0} \atop {4(-x+y)=-8}} \right. \\\left \{ {{x+y=0} \atop {-x+y=-2}} \right.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v09osinac9b00318ootnqrvywml8chd04m.png)
Now, summing both equations we have:
![2y=-2\\y=-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/61h91kxr5gbtp6uwk88wet4r6wxvyvn7dd.png)
Replacing this value in a equation we have:
![3x+3y=0\\3x+3(-1)=0\\3x-3=0\\x=(3)/(3)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mw85qhxep4gweutxei04tlc66khiazpr43.png)
Now, we have to find the other system that it's satisfied by
and
.
![\left \{ {{3x+3y=0} \atop {7x-y=8}} \right.\\3(1)+3(-1)=0\\3-3=0\\0=0\\7(1)-(-1)=8\\7+1=8\\8=8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zeu94wuyt5955d8pxwqsbnsqtllzjn4vko.png)
As you can see, the first system is equivalent because it has the same solution as the given system of equations.
Therefore, the correct answer is the first one.